2021
DOI: 10.1001/jamadermatol.2021.2551
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Gender-Affirming Hair Removal and Mental Health Outcomes

Abstract: Gender-affirming medical care is essential for addressing the mental health burdens of transgender and gender-diverse (TGD) populations. 1 Gender-affirming hair removal (GAHR) procedures, including electrolysis and laser hair removal, are desired by nearly 90% of TGD people. 2 However, such services are covered by only 4.6% of insurance plans, 3,4 possibly owing in part to limited evidence of their menatal health benefits. In this study, we investigated the association between GAHR and mental health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 5 publications
0
25
0
1
Order By: Relevance
“…In states with coverage for some but not all gender-affirming surgical procedures, state and federal government funding is necessary to allow Medicaid to cover the increased cost of expanding coverage for procedures, such as facial gender surgery. Investments made in this regard could lead to greater economic growth and productivity due to the impact on a TGD person’s ability to avert physical and psychological trauma, secure employment, and improve overall mental health 20,21 . Expanding Medicaid coverage in these ways is critical to ensuring timely access to gender-affirming surgical procedures across the nation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In states with coverage for some but not all gender-affirming surgical procedures, state and federal government funding is necessary to allow Medicaid to cover the increased cost of expanding coverage for procedures, such as facial gender surgery. Investments made in this regard could lead to greater economic growth and productivity due to the impact on a TGD person’s ability to avert physical and psychological trauma, secure employment, and improve overall mental health 20,21 . Expanding Medicaid coverage in these ways is critical to ensuring timely access to gender-affirming surgical procedures across the nation.…”
Section: Discussionmentioning
confidence: 99%
“…Investments made in this regard could lead to greater economic growth and productivity due to the impact on a TGD person's ability to avert physical and psychological trauma, secure employment, and improve overall mental health. 20,21 Expanding Medicaid coverage in these ways is critical to ensuring timely access to gender-affirming surgical procedures across the nation. For those without the means to migrate to another state, which likely applies to many Medicaid patients who are already low-income, lack of coverage within their home state may mean a complete inability to access this essential care that their wealthier counterparts may be able to have.…”
Section: Discussionmentioning
confidence: 99%
“…Gender affirming hormone therapies have also led to an increase in body image and self-esteem ( 87 ). Similarly, hair removal procedures (desired by nearly 90% of transgender people) were associated with significant mental health benefits ( 88 , 89 ).…”
Section: Medical Care For Transgender Pain Patientsmentioning
confidence: 99%
“…61 Gender-affirming hair removal may be associated with improved mental health outcomes and well-being. 62,63 Twice daily application of topical eflornithine may reduce facial hair although is no longer sold commercially in Australia and must be privately compounded. 64 Longer-lasting hair removal techniques such as laser depilation or electrolysis may obviate the need for frequent shaving, waxing or chemical depilation.…”
Section: Persistent Hirsutismmentioning
confidence: 99%
“…A survey demonstrated that 85% of transwomen desired hair removal, with 94% indicating the face as the indicated site of excess hair 61 . Gender‐affirming hair removal may be associated with improved mental health outcomes and well‐being 62,63 . Twice daily application of topical eflornithine may reduce facial hair although is no longer sold commercially in Australia and must be privately compounded 64 .…”
Section: Dermatological Considerations In Oestrogen and Antiandrogen ...mentioning
confidence: 99%